2005
DOI: 10.1051/0004-6361:20053028
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band photometric colors and effective temperature calibrations for late-type giants

Abstract: We present new synthetic broad-band photometric colors for late-type giants based on synthetic spectra calculated with the PHOENIX model atmosphere code. The grid covers effective temperatures T eff = 3000 . . . 5000 K, gravities log g = −0.5 . . . +3.5, and metallicities [M/H] = +0.5 . . . −4.0. We show that individual broad-band photometric colors are strongly affected by model parameters such as molecular opacities, gravity, microturbulent velocity, and stellar mass. Our exploratory 3D modeling of a prototy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 68 publications
7
93
0
Order By: Relevance
“…This is more easily seen in Fig. 8, which shows the 9 Theoretical magnitudes calculated from PHOENIX models and calibrated against observational data suggest that all late-M giants have (J − K) 0 ∼ 1.3 (Kučinskas et al 2005). The calibration of Groenewegen (2004), based on older models, gives (J − K) 0 = 1.37 for dustfree M7 stars.…”
Section: Spatial Distribution Of Rsgsmentioning
confidence: 77%
“…This is more easily seen in Fig. 8, which shows the 9 Theoretical magnitudes calculated from PHOENIX models and calibrated against observational data suggest that all late-M giants have (J − K) 0 ∼ 1.3 (Kučinskas et al 2005). The calibration of Groenewegen (2004), based on older models, gives (J − K) 0 = 1.37 for dustfree M7 stars.…”
Section: Spatial Distribution Of Rsgsmentioning
confidence: 77%
“…Line formation in the 1D model atmospheres: influence of the mixing-length parameter α MLT According to the classical Schwarzschild criterion, 1D LHD models of the red giant studied here are convectively stable in the outer photospheric layers (log τ Ross < ∼ 1), irrespective of the mixing length parameter, α MLT (Kučinskas et al 2005;Ludwig & Kučinskas 2012). Since line formation depths typically never 3 Including the indirect temperature dependence via electron pressure.…”
Section: Abundance Corrections At 25 μMmentioning
confidence: 91%
“…In one of the early attempts, Kučinskas et al (2005) have found that convection may noticeably alter the thermal structure of the red giant atmosphere which, in turn, may affect the spectral energy distribution of the emerging radiation field. This may yield a difference of ∼0.2-0.3 mag in broad-band photometric colors predicted by the 3D hydrodynamical and classical 1D models.…”
Section: Introductionmentioning
confidence: 99%
“…To derive the colour excesses for RSGs, an estimation of Kučinskas et al (2005) there is no explicit relation between spectral type and (J − K) 0 , as the authors classify their stars on a temperature scale. We transform these into spectral types using the derived temperatures Groenewegen (2004) and Levesque et al (2005) where available, and using the data from Cenarro et al (2001) everywhere else (marked with an asterisk in Table A.1).…”
Section: Appendix A: Intrinsic Infrared Colour Calibration For the Rementioning
confidence: 99%